Swelling of ultrathin crosslinked polyamide water desalination membranes1. Issue 6 (27th December 2012) - Chan, Edwin P.; Young, Allison P.; Lee, Jung‐Hyun; Chung, Jun Young; Stafford, Christopher M.
Abstract We study the water swelling behavior of semiaromatic crosslinked polyamide (PA) ultrathin films to characterize the network properties of the polymer. Specifically, we use X‐ray reflectivity to measure film thickness increase and polymer density decrease of the PA films due to swelling. With the aid of a modified Flory–Rehner theory used to describe the constrained swelling behavior of polymer networks, we are able to extract the Flory interaction parameter and the monomer units between crosslinks by performing the swelling experiments at different levels of hydration. © 2012 Wiley Periodicals, Inc. J Polym Sci Part B: Polym Phys, 2013